2001
DOI: 10.1034/j.1398-9995.2001.056008763.x
|View full text |Cite
|
Sign up to set email alerts
|

Three cases of childhood nocturnal asthma due
to buckwheat allergy

Abstract: Background: Buckwheat¯our (BF) is known as a potent food allergen. Sensitization to it usually occurs by ingestion but also by inhalation in occupational or domestic exposure. Buckwheat chaff-stuffed pillows (BCP) can be contaminated with BF during the process of pilling, and many Korean children and adults use BCP for health reasons. Methods and Results: We here present three cases of BF allergy in children using BCP, who had been treated as nonatopic asthmatics after undergoing the routine allergy skin tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Subjects who had respiratory symptoms used BW husk pillows more often compared with those who did not have respiratory symptoms. One case report suggested that a small amount of BW flour attached to a BW husk pillow could induce sensitization and cause nocturnal asthma7). A case report in 2009 from the United States suggested that initial ingestion of BW food caused anaphylaxis after previous sensitization by BW husk pillow8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects who had respiratory symptoms used BW husk pillows more often compared with those who did not have respiratory symptoms. One case report suggested that a small amount of BW flour attached to a BW husk pillow could induce sensitization and cause nocturnal asthma7). A case report in 2009 from the United States suggested that initial ingestion of BW food caused anaphylaxis after previous sensitization by BW husk pillow8).…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports document immune events related to using BW husk pillows. In 1 case report, 3 patients had chronic asthma due to exposure to BW husk pillows, and in another case report, 2 patients were sensitized to BW after using BW husk pillows78).…”
Section: Introductionmentioning
confidence: 99%
“…8 Many Korean children traditionally use buckwheat chaff-stuffed pillows (BCP) contaminated with buckwheat flour during the process of pilling. Lee et al 73 described three children whose nocturnal asthmatic symptoms improved during 7 days of BCP elimination, and asthmatic responses were observed by bronchial provocation tests with homemade buckwheat extract. All three children showed positive skin reactions and serum IgE antibodies to buckwheat.…”
Section: Buckwheatmentioning
confidence: 98%
“…Buckwheat flour and buckwheat chaff-stuffed pillows have been shown to be able to sensitize via the respiratory tract [74,75], and cases of either respiratory or skin symptoms upon contact with ground buckwheat have been reported [76]. Importantly, recent observations show that buckwheat airborne allergy may precede by years the onset of food allergy [77].…”
Section: Evidence For Adult Extra-intestinal Sensitization To Food Almentioning
confidence: 99%